PERSEPSI MAHASISWA FAKULTAS EKONOMI UNIVERSITAS SYIAH KUALA TERHADAP PERBANKAN SYARIAH SEBAGAI LEMBAGA KEUANGAN SYARIAH - Suparno Suparno (Jurnal Telaah dan Riset Akuntansi, 2009)
The purpose of this research was to find out  the perception of economic students to banking syari’a as syariá finance institution. The population of this research was the economic student of syiah kuala university level 2003-2007  amounted to 2267 person in three pieces that is accounting department, management department and developed economic department. Based on stratified random sampling 100 person of student were chosen to be target population. Analysis unit was student who had the use of banking syariah product . Methods of data Analysis was validity analysis, reability analysis and proportion analysis.Result of research that used proportion analysis show that the economic student of syiah Kuala University had good (positive) perception to banking syariah. Keywords; perception, syariah banking.